Modern diagnostics in IgE-mediated cow’s milk allergy (Journal of Medical Science, 2022)
Cow’s milk allergy (CMA) is the most common food allergy in infants and young children. Allergic reactions may vary from mild to severe, such as an anaphylactic shock. In the case of a suspected CMA diagnosis, skin prick tests (SPT), immunoassays of specific IgE (sIgE) in blood serum (in vitro tests) and oral food challenge (OFC) tests can be performed. SPT wheal diameter and the level of serum specific IgE to milk do not correlate with the severity of clinical symptoms, and the OFC procedure is frequently difficult or even impossible in practice. Therefore, component-resolved diagnostic (CRD) tests are a new diagnostic tool, which allows a better correlation of laboratory test results with the observed clinical symptoms as well as identification of the triggering allergens.